Study of the modulator effect of oil chia (Salvia hispanica L.) associated with benzo(a)pyrene and doxorubicin hydrochloride (Research, Society and Development, 2022)
Chia (Salvia hispanica L.) is a Mexican plant belonging to the Lamiaceae family, representing one of the four main seeds cultivated by pre-Columbian peoples, mainly the Aztecs who used it as a medicine and nutritional component. Currently, it has been rediscovered, they are rich in polyunsaturated fatty acids, with antioxidant activity and essential compounds for organism maintenance. Various benefits are attributed to this plant including the reduction of cardiovascular problems, psoriasis, depression, Alzheimer’s, diabetes, arthritis and cancer. Considering the widespread use of chia oil (OC) in today’s society, it was justified to investigate the modulating effect of this oil when combined with benzo(a)pyrene and doxorubicin hydrochloride, using the SMART (Somatic Mutation and Recombination Test), a test able to detect mutation and somatic recombination activities, with loss of heterozygosis, which can be observed in the forms of different trichomes present in the wings of Drosophila melanogaster. The results obtained indicate that chia oil reduced the frequency of mutations by 97% in the number of spots induced by benzo(a)pyrene (BaP) and doxorubicin hydrochloride (DRX), showing an antigenotoxic effect.